Personality traits and work-related compulsive technology use: An organizational perspective - Thomas, Basil John; Thomas, Basil John (International Journal of Psychosocial Rehabilitation, 2020)
The development of technology has led to the expansion of automatic and complex technology- usage behavior. As a result, individuals are likely to feel compelled to interact with the system, which is referred as a compulsive technology use. The current study attempts to find whether in organizational context employees who frequently engage in work-related compulsive technology use have common personality traits, while also investigates whether work-related compulsive technology use leads to positive firm performance. Data was originated from online survey conducted with 332 employees of 8 construction companies in the Middle East and then used in multiple hierarchical regression analysis. The findings reveal that among the personality factors, Extraversion, Agreeableness, and Openness positively predict Task CTU, while Neuroticism is negatively related to it. Conversely, Consciousness does not have an influence on Task CTU. As an external variable, Computer Self- Efficacy positively and strongly predicts Task CTU. Finally, Task CTU is positively related to firm performance, but not employee performance. The other findings are discussed further.